ANALISA PENGARUH VARIASI SUSUNAN TERHADAP KEMAMPUAN UNJUK KERJA POMPA HYDRAM DITINJAU DARI ASPEK TINGGI TERJUNAN AIR - Sutanto, Rudy; Wirawan, Made (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
Cultivation activities, both in the development of food crops, horticulture, livestock and plantations. Availability of water is a strategic factor. Specific areas adjacent to the water source or location are under the eyes water, water needs are less of a problem. However, the ground reality is not always flat; there is the hilly or bumpy. Land surface area is higher than the water source and the bumpy areas will have trouble getting a continuous supply of water. Therefore need to find an alternative to reduce the burden. One alternative is that hydram pump hydraulic work without using gasoline. Hydram pump was applied to a small debit them to raise water and drinking water needs of households. However, the use for irrigation in dry land agriculture that requires a large output flow is unknown. The method used in this research is to create models in the laboratory to simulate the independent variables of pressure (high falling) water flow while bound variables measured include debit and results of hydraulic pressure. The results of experiments that analyzed the correlation between independent variables and the variables are bound to get hydram pump efficiency. Pumps that were realized and tested in the laboratory have the following specifications: input = 1.5 inch diameter; output diameter = 0.5 inches; step on the valve piston waste = 5 mm; air tube diameter = 3 inches; air tube length = 24 cm ; material with galvanized pipe, construction of hydram pump consisting of the first arrangement of input - waste valves - compressor (ILK) and the second arrangement of input - compressor - waste valve (IKL). Pump of hydram with arrangement ILK has the ability to better performance when compared with the composition of IKL. Where pump of hydram with the composition of ILK has the best efficiency at 2.5 meters high waterfall with a debit enter 2.458 liters / sec discharge output capable of being lifted by a pump at 0087 liters / sec while the high lift or vertical height of the pump which is equal to 30 meters and efficiency pump of hydram which is equal to 13.6%.